Dietary inadequacy in Tanzania is linked to the rising cost of nutritious foods and consumption of food-away-from-home - Ignowski, Liz; Belton, Ben; Tran, Nhuong; Ameye, Hannah (Elsevier, 2023)
This study contributes to the growing literature on dietary quality and accessibility in the Global South. We analyze the nutrition implications of changing dietary patterns between 2008 and 2019 in one of Africa's largest and fastest growing economies, Tanzania, and compare patterns at national and sub-national scales. We find that: (1) Rising incomes have not been associated with marked increases in the diversity of food consumed at home; (2) Consumption of food away from home has increased dramatically; (3) Most food consumed in Tanzanian homes is purchased instead of self-produced; (4) There have not been clear improvements in the adequacy of micronutrient consumption obtained from food eaten at home; (5) The most affordable sources of key micronutrients, including nutrient dense foods such as dried fish, have become more expensive. Our findings indicate that in Tanzania the amount and diversity of nutritious foods eaten at home have not improved with rising incomes, but consumption of energy-dense processed foods eaten away from home has increased rapidly, likely reflecting differences in convenience and relative prices. To improve Tanzanian diets in coming years, coordinated nutrition-sensitive policy actions will be required on both the supply- and demand-sides.